PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS NASABAH PADA PT. ASURANSI UMUM BUMIPUTERA MUDA 1967 CABANG PEKANBARU - Wulan Sari; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this study was to analyze the Customer Relationship Management and Customer Loyalty at PT. General Insurance Bumiputera Muda 1967 Pekanbaru Branch and see the effects. The study concluded that CRM at PT. General Insurance Bumiputera Muda 1967 Pekanbaru Branch which include dimensions, people, process and technology. Overall is considered to be good. Customer loyalty in the PT. General Insurance Bumiputera Muda 1967 Pekanbaru Branch is seen from the dimensions make the purchase again, refer to others, buy poduk between the lines and the desire to remain a customer also rated high. The results of the data analysis by SPSS, CRM has a strong influence on customer loyalty. CRM variables have a positive influence and significant to variable customer loyalty in the PT. General Insurance Bumiputera Muda 1967 Branch Pekanbaru, which means when the CRM was increased then it will also lead to an increase in customer loyaltyKeywords: Customer Relationship Management, customer loyalty, PT. General Insurance Bumiputera Muda 1967